1955
DOI: 10.1113/jphysiol.1955.sp005349
|View full text |Cite
|
Sign up to set email alerts
|

The sense of pitch and local increase in threshold

Abstract: The pitch of a pure tone depends basically on its frequency, but it can sometimes be modified by the intensity of the tone. Hitherto, in work on the modifying influence of intensity (e.g. Stevens, 1935;Snow, 1936;Morgan, Garner & Galambos, 1951) the subjects have been chosen for their normality of hearing. It is reported by Morgan et al. (1951) that it is typical for such subjects to find pitch almost independent of intensity. In the present work, the effect of intensity on pitch for subjects with slight heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1956
1956
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Consequently, in our current results, the pitch matches may have been influenced by (mainly highfrequency) hearing loss in the better ear. However, we know that the influence of loudness on pitch perception is negligible in the tested range (50-65 dB HL) [Strange, 1955]. Second, there was a small sample size (CI422 group: n = 8, CI512 group: n = 6).…”
Section: Methodological Considerationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, in our current results, the pitch matches may have been influenced by (mainly highfrequency) hearing loss in the better ear. However, we know that the influence of loudness on pitch perception is negligible in the tested range (50-65 dB HL) [Strange, 1955]. Second, there was a small sample size (CI422 group: n = 8, CI512 group: n = 6).…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…The manually presented acoustic stimuli had a minimum duration of 500 ms. For the first run of measurements per electrode, we adjusted the level of a 1-kHz acoustic tone (median 60 dB HL, range 50-65 dB HL) to match it to the loudness of the electric stimulus in the CI ear (C-level of the most frequently used program). In this range (50-65 dB HL), the influence of loudness on pitch perception is negligible [Strange, 1955]. The task was to compare the pitch of two acoustic stimuli to the pitch of the electric stimulus and select the acoustic stimulus with greatest similarity in pitch.…”
Section: Stimuli and Experimental Designmentioning
confidence: 99%
“…These results show that at frequencies between 1000 and 8000 c/s it is indeed abnormal for the pitch of a pure tone to be dependent on intensity to any great extent. The author's earlier work (Strange, 1955) suggested very strongly that this was so, both because the magnitude of the pitch changes increased with the hearing loss, and because pitch was almost independent of intensity outside a limited frequency range close to that of the threshold defect. It is now shown that in the absence of such a dip in the audiogram, and of any other obvious threshold defect, the pitch of pure tones is hardly affected by intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Plotted on a logarithmic diagram of frequency against intensity, a straight line may be fitted to these points, whose slope is a measure of the degree of dependence of pitch on intensity. The details of this calculation are in the previous paper (Strange, 1955). Tests were performed for each subject with the standard frequency 4000 and 6000 c/s.…”
mentioning
confidence: 99%
“…Strange (158) has reported an experiment in which she studied the effect of intensity on pitch in subjects with a dip between 3000 and 6000 c.p.s. in the audiogram of at least one ear.…”
Section: Frequency Discrimination and Pitchmentioning
confidence: 99%